Politics Of Law Human Rights Protection In Indonesia - Pradikta Andi Alvat (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aims to know how political development of legal protection of human rights in Indonesia and political objectives of the legal protection of human rights itself. The research method using normative juridical approach. Specification of the research is descriptive. Provide an overview and critical analysis and conclusions of the research object. Source data using secondary data sources through books and legislation. The data collection method through the study of literature. Analysis of data using qualitative approach. The results showed that the political development of the legal protection of human rights has undergone discourse tight since the formulation of the Constitution and found basic juridical-constitutional is ideal since the reform era with the birth of Chapter XA in the constitution on human rights, born Law of Human Rights, and the formation of the court of HAM. The purpose of a political human rights protection law contains three dimensions, namely the dimensions of philosophical, sociological dimension and juridical dimension.Keywords: Protection Of Human Rights; Political Law; State Law.